Pengaruh Kekuatan Aspal Dengan Penambahan Abu Cangkang Kemiri Sebagai Pengganti Filler Pada Lapis AC - WC - Sainuddin Sainuddin (Universitas Sulawesi Barat, 2024)
West Sulawesi holds great potential in the field of candlenut farming, ranking second in Indonesia by producing 10 tons per year. This has an impact on the large amount of candlenut waste produced, especially in the candlenut shell part. One way to overcome this is to use candlenut shell ash as a substitute for filler in the asphalt layer. The aim of this research is to determine the effect of using candlenut shell ash waste as a filler on the type of Asphalt Concrete - Wearing Course mixture with variations in the addition of 2%, 3% and 4% filler. Apart from that, this research also aims to analyze the effect of using 6.4% asphalt content on the mixture. The research that has been carried out shows that the addition of candlenut shell ash as a filler to the Asphalt Concrete - Wearing Course mixture with an asphalt content of 6.4% is used. The results obtained were that, while the 2% and 3% variations had 4% fulfilled the 2018 General Bina Marga specifications and could be used as a mixture.